Impact of Human Activities on Lake Landscapes and Aquatic Fauna: A Case Study of Kechana Lake - Pokhrel , Puspa Lal (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2018)
Lakes are considered to be one of the most threatened of various major natural ecosystems and are claimed to deserve a highest priority for conservation and wise use. Kechana Lake is the lowest land wetlands of Nepal. Kechana and associated lakes lie in Jhapa district that are adjoining to the Indian border. It has a lentic environment. Kechan Lake is originated due to river process. Geographically it is known as Oxbow lake. This lake is Eutrophic due to the contamination with nutrient rich resources. The present status of faunal diversity surrounding the lake area seemed very poor. There are no trees, bushes and shrubs in the lake periphery and there is absence of aquatic weeds as well as floating flora on the surface water in the lake. These floras serve as food for aquatic fauna and make easier protect the aquatic ecosystem.